Creative play therapy with adolescents and adults : moving from helping to healing - Thomas, Denis' A.; Morris, Melanie H. (New York, NY : Routledge, 2020)
"This user-friendly manual shows mental health professionals how to implement play therapy with adolescents and adults and how to conceptualize client struggles using a wealth of creative approaches. Creative Play Therapy for Adolescents and Adults follows a seven-stage process for professionals to address clients' core needs and establish an empathic therapeutic relationship. The book charts the stages of play therapy and explores a range of expressive arts including art, drama, dance, writing, and sand play.This book will be of interest to a wide range of mental health professionals as it encourages a more creative career and lasting, tangible progress in clients"--
OCLC-licensed vendor bibliographic record.
Keywords: Play therapy; PSYCHOLOGY / Psychotherapy / Counseling; PSYCHOLOGY / Psychotherapy / General; PSYCHOLOGY / Mental Health